2015
DOI: 10.1002/joc.4472
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Caribbean low-level jet during boreal winter: large-scale forcings

Abstract: An index capturing the anomalies of the zonal wind at 925 hPa from 1950 to 2010 was defined to explore the relationship between the fluctuations of the Caribbean low-level jet (CLLJ) and the main climate variability modes affecting the Intra-Americas Sea Region. El Niño Southern Oscillation (ENSO) events, here defined using the Niño 3.4 index, are found to be the most important variability modes for the jet anomalies, in agreement with previous studies. However, the Pacific Decadal Oscillation (PDO) and the Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
1
20
0
1
Order By: Relevance
“…6a). The subsequent reduction in Caribbean moisture transport is attributed to the response of the deceleration of the CLLJ under warm ENSO conditions in winter time (Amador et al, 2006;Amador, 2008;Maldonado et al, 2015). Stronger differences are detected as the first rainy season starts, with a greatly reduced contribution from the southwest Caribbean as shown by the dark blue shading in Fig.…”
Section: Response Of Oceanic Moisture Sources To Enso Forcingmentioning
confidence: 91%
“…6a). The subsequent reduction in Caribbean moisture transport is attributed to the response of the deceleration of the CLLJ under warm ENSO conditions in winter time (Amador et al, 2006;Amador, 2008;Maldonado et al, 2015). Stronger differences are detected as the first rainy season starts, with a greatly reduced contribution from the southwest Caribbean as shown by the dark blue shading in Fig.…”
Section: Response Of Oceanic Moisture Sources To Enso Forcingmentioning
confidence: 91%
“…The wind data is used to calculate the CLLJ index as in Amador (2008) and Maldonado et al (2016). Based on the methodology developed in Alfaro (2014), and also applied by Solano (2015), the daily precipitation times series are filtered using a running triangular weight average with a window of 31 days, to avoid or minimise interruptions of the MSD due to weakening of the trades and/or approaching of the ITCZ, as suggested by Ramírez (1983) and Alfaro (2014).…”
Section: T Maldonado Et Al: Interannual Variability Of the Midsummementioning
confidence: 99%
“…This tripolar setting is located in the region where the PDO develops. The PDO has shown more influence in the southern USA and northern Mexico than in Central America (Muñoz et al, 2010;Maldonado et al, 2016), and that could be the reason that its influence is observed in the second mode. The Y loadings in both cases (Fig.…”
Section: Canonical Correlation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Wind speeds around the 925 hPa level peak twice a year, during February and July. This low‐level wind current exhibits a semiannual cycle extensively reported in previous studies [ Amador , , Amador et al ., , ; Wang , ; Amador , ; Muñoz et al ., ; Whyte et al ., ; Cook and Vizy , ; Maldonado et al ., ]. In the literature this wind current is often known as the Caribbean low‐level jet (CLLJ).…”
Section: Introductionmentioning
confidence: 99%